Moving Washington timeline : the first century of the Washington State Department of Transportation, 1905-2005 - Crowley, Walt; Oldham, Kit (HistoryLink : Distributed by the University of Washington Press, 2005)
"This book retraces how the leaders and employees of the Washington State Department of Transportation and their predecessors helped to shape Washington's transportation system during a century of technological revolution and dramatic transformation of its communities and landscapes." "Moving Washington Timeline was prepared for the Washington State Department of Transportation with the support of private donors and a Federal Highway Administration grant to commemorate the creation of the.